2008
DOI: 10.1002/uog.5390
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of three‐dimensional sonographic measurements in early pregnancy using virtual reality

Abstract: Objective To establish the reliability of three-dimensional (3D) ultrasound measurements in early pregnancy using a virtual reality system (the Barco I-Space). MethodsThe study included 28 pregnancies with gestational ages ranging from 6 to 14 (median, 10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 21 publications
1
73
1
Order By: Relevance
“…Studies using this VR technology have demonstrated that it provides additional insights, [16][17][18][19][20] especially where structures that need depth for accurate interpretation of size and position are concerned. Verwoerd et al 20 already demonstrated the reliability of this system in measuring standard human embryonic biometry. The volume-measuring tool of V-Scope is a new development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using this VR technology have demonstrated that it provides additional insights, [16][17][18][19][20] especially where structures that need depth for accurate interpretation of size and position are concerned. Verwoerd et al 20 already demonstrated the reliability of this system in measuring standard human embryonic biometry. The volume-measuring tool of V-Scope is a new development.…”
Section: Discussionmentioning
confidence: 99%
“…These data sets were obtained in another study to evaluate embryonic growth and development by Verwoerd et al 20 We used the yolk sac as our object of interest since it is an easy to identify, well-defined, fluid-filled structure. All measurements using the four different techniques were performed off-line (Figure 3) as described in the in vitro part and repeated three times; mean values of these three assessments were used for comparison.…”
Section: In Vivo Studymentioning
confidence: 99%
See 1 more Smart Citation
“…18 High precision was achieved using the means of measurements performed in triplicate. Furthermore, the assessment of long-term RBC folate reflects the periconception maternal folate status.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…9 In a research setting, the 3D_VR_US has already been successfully applied for determining various firsttrimester reference values, and in individual cases of complex congenital malformations, 3D_VR_US supported the diagnosis by adding clinically relevant details. [10][11][12][13][14][15][16] Although clinicians rapidly adopted conventional 3D_US upon its introduction at the end of the 1990s without formal evaluation, 7 this study aims to provide diagnostic evidence to support a similar decision on 3D_VR_US. The application is investigated for the use of first-trimester screening for structural abnormalities.…”
Section: Introductionmentioning
confidence: 99%